2-3(2x-1)=3x-(x+2)

Simple and best practice solution for 2-3(2x-1)=3x-(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-3(2x-1)=3x-(x+2) equation:



2-3(2x-1)=3x-(x+2)
We move all terms to the left:
2-3(2x-1)-(3x-(x+2))=0
We multiply parentheses
-6x-(3x-(x+2))+3+2=0
We calculate terms in parentheses: -(3x-(x+2)), so:
3x-(x+2)
We get rid of parentheses
3x-x-2
We add all the numbers together, and all the variables
2x-2
Back to the equation:
-(2x-2)
We add all the numbers together, and all the variables
-6x-(2x-2)+5=0
We get rid of parentheses
-6x-2x+2+5=0
We add all the numbers together, and all the variables
-8x+7=0
We move all terms containing x to the left, all other terms to the right
-8x=-7
x=-7/-8
x=7/8

See similar equations:

| 2x+18=7x-42 | | 6/9=t/9 | | -1.75m=26.25 | | J+3+2j=2j-12 | | 4n+23=2n+25 | | 3x+2+3x+14x-2=180 | | 9=6-11y+8y | | -5f=-4-6f | | 5.99+1.99x=7.99+1.49x | | 9=6-11y+89 | | 5x+7=8x-9-5x | | 2/3(x-7)=12 | | 4(g+4)=2020 | | -21-4x+6x=11 | | -17-2x=-6x | | 2(3a-7)=13 | | 5n+2n=92 | | 5x+8=6(x+4) | | 7(1-3x)=9x-53 | | 9x-15=6x-12 | | v−–22=88 | | 7s-19-10s=13+s | | 5d-8=4+7d | | 3v−2=7 | | 9a−7a=3a−33+2a | | –3c+11c=–16 | | 24=v+14 | | -7y+7=24y-4 | | 2x+7−5x+8=3(5+6x)−12x= | | 50=40a | | 5/6x+21=1/6x+17 | | 6(3-x)=6 |

Equations solver categories